Pregnancy incidence and associated risk factors of dichorionic triamniotic triplet under assisted reproduction: A large sample of clinical data analysis - Liu, Shuhua; Xu, Qianhua; Wang, Yafen; Song, Bing; Wei, Zhaolian (Frontiers in Endocrinology, 2023)
Background Dichorionic triamniotic (DCTA) triplet pregnancies are rare in spontaneous pregnancy. The aim was to characterize the incidence and risk factors of DCTA triplet pregnancies after assisted reproductive technology (ART). Methods A retrospective analysis of 10,289 patients, including 3,429 fresh embryo transfer (ET) cycle and 6,860 frozen ET cycle, was performed from January 2015 to June 2020. The effect of different ART parameters on the incidence of DCTA triplet pregnancies was evaluated by multivariate logistic regression analyses. Results Among all clinical pregnancies after ART, the incidence of DCTA was 1.24%. 1.22% occurred in the fresh ET cycle, while 1.25% occurred in the frozen ET cycle. The number of ET and cycle type has no effect on the occurrence of DCTA triplet pregnancies (p = 0.987; p = 0.056, respectively). There were significant differences in DCTA triplet pregnancies rate among receiving intracytoplasmic sperm injection (ICSI) and receiving in vitro fertilization (IVF) [1.92% vs. 1.02%, p < 0.001, OR = 0.461, 95% confidence interval (CI) 0.315–0.673], blastocyst transfer (BT) versus cleavage-ET (1.66% vs. 0.57%, P < 0.001, OR = 0.329, 95% CI 0.315–0.673), and maternal age ≥ 35 years versus maternal age < 35 years (1.00% vs. 1.30%, P = 0.040, OR = 1.773, 95% CI 1.025–3.066). Based on the regression analysis of cycle type, DCTA triplet pregnancies rate was higher in maternal age < 35 years than in maternal age ≥ 35 years (1.35% vs. 0.97%, P < 0.001, OR = 5.266, 95% CI 2.184–12.701), BT versus cleavage-ET (1.47% vs. 0.94%; P = 0.006, OR = 0.346, 95% CI 0.163–0.735), and receiving ICSI was higher than receiving IVF (3.82% vs. 0.78%, p < 0.001, OR = 0.085, 95% CI 0.039–0.189) in fresh ET cycle. However, DCTA triplet pregnancies rate did not show difference in maternal age, insemination methods, and number of ET, and only BT was found to be associated with a higher DCTA triplet pregnancies rate in the frozen ET cycle (1.73% vs. 0.30%, p < 0.001, OR = 0.179, 95% CI 0.083–0.389). Conclusion The prevalence of DCTA triplet pregnancies has increased after ART. Maternal age < 35 years, BT, and receiving ICSI are risk factors for DCTA triplet pregnancies, also in fresh ET cycle. However, in frozen ET cycle, BT is an independent risk factor for increased DCTA triplet pregnancies rate.